2007
DOI: 10.1002/pat.900
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardancy of polycarbonate enhanced by adding fly ash

Abstract: We have developed a flame-retardant polycarbonate resin whose flame retardancy is greatly enhanced by adding fly ash (a by-product from thermal power plants). Fly ash with comparatively small average particle sizes (<10 mm) raised the flame retardancy of polycarbonate because of the hydrogen bond that forms between the polycarbonate and the hydroxy group on the fly ash surface. This bond primarily improves the heat resistance of the polycarbonate and also isomerizes the polycarbonate to promote carbonization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Usta (2012) showed that FA significantly enhanced fire resistance and thermal stability of polyurethane foams due to the inert nature of FA with fire. A similar effect was found with polycarbonate (Soyama et al 2007). …”
Section: Polymer Composite Materialssupporting
confidence: 84%
“…Usta (2012) showed that FA significantly enhanced fire resistance and thermal stability of polyurethane foams due to the inert nature of FA with fire. A similar effect was found with polycarbonate (Soyama et al 2007). …”
Section: Polymer Composite Materialssupporting
confidence: 84%
“…7,9,1518 For example, fly ash could improve the flame retardancy by promoting carbonization and forming hydrogen bond between the hydroxyl group on the fly ash surface and the carbonate group of the polycarbonate. 16 Graphite oxide could increase the flame retardancy through forming a continuous protective char layer, which acted as a thermal insulator and a mass transport barrier. 7 Recent studies indicate that combination of physical effect and chemical reaction from inorganic materials may have synergistic effect to improve the flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, it would be necessary to develop inorganic compounds which not only can improve flame retardany for PC, but also are environment friendly. 7,9,[15][16][17][18] For example, fly ash could improve the flame retardancy by promoting carbonization and forming hydrogen bond between the hydroxyl group on the fly ash surface and the carbonate group of the polycarbonate. 16 Graphite oxide could increase the flame retardancy through forming a continuous protective char layer, which acted as a thermal insulator and a mass transport barrier.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] In this investigation we studied the effect of fly ash with three varying particle sizes and concentration on the properties of PTT. Recently many investigators studied the effect of fly ash on the properties of thermoplastics and thermosets [8][9][10][11][12][13][14][15]. Fly ash is the finely divided mineral residue resulting from the burning of pulverised coal in thermal power stations.…”
Section: Introductionmentioning
confidence: 99%